Identification and mapping of the nursing diagnoses and actions in an Intensive Care Unit. - Salgado, Patricia de Oliveira; Chianca, Tânia Couto Machado (Revista Latino-Americana de Enfermagem (RLAE))
This is a descriptive study with the aim of examining the nursing diagnoses labels and actions prescribed by nurses in the clinical records of patients hospitalized in an Adult Intensive Care Unit. A sample of 44 clinical records was obtained and a total of 1087 nursing diagnoses and 2260 nursing actions were identified. After exclusion of repetitions 28 different nursing diagnoses labels and 124 different nursing actions were found. Twenty- five nursing diagnoses labels were related to human psychobiological needs and three to psychosocial needs. All the nursing actions were mapped to the physiological needs and also to interventions of the Nursing Interventions Classification-NIC. Concordance of 100% was obtained between the experts in the validation process of the mapping performed, both for the nursing diagnoses labels and actions. Similar studies should be conducted for the identification and development of nursing diagnoses and actions.